The Acoustics of Crime : the New Science of Forensic Phonetics - Hollien, Harry (Applied psycholinguistics and communication disorders., 1990)
There are many reasons for writing a book; this one was conceived and devel oped mainly for two. First, a new area has emerged from within the forensic sciences-that of forensic phonetics. As with all new specialties, it is necessary to define it, identify its boundaries, justify its importance and compile a list of the elements it encompasses. This book attempts to outline these several rela tionships. Second, over the past decade I have become fascinated with forensics in general and the rapidly expanded subarea of forensic phonetics in particular. Admittedly, the latter field is one that is not as yet sufficiently appreciated-and much more needs to be known about its nature and extent. Yet, I have found it to be a most enjoyable area of study and my attempts to describe its domains were quite informative. It was especially interesting to struggle with the interfaces between forensic phonetics and related fields, and discover how they overlap. Only a few comments will be made about the book's contents here in the preface. For one thing, they are described in some detail in the first chapter.